The intersection of gout and metabolic syndrome: a study on prevalence and clinical correlates - Zahra Bagheri-Hosseinabadi; Arife Mehdizadeh Tehrani; Mohammad Taha Akbari Jour; Mitra Abbasifard (Advances in Rheumatology, 2026)
Abstract Background Elevated urate in gout patients is linked to a higher risk of metabolic syndrome (MetS), yet research on MetS prevalence and determinants in this group remains limited. This study aims to fill this gap by investigating the frequency of MetS and identifying its contributing factors in individuals with gout. Methods In this study, 150 cases with gout and 500 control subjects were recruited. MetS diagnosed was accomplished using National Cholesterol Education Program - Adult Treatment Panel III (NCEP-ATP III) criteria. Results The frequency of MetS was 32 (21.33%) and 78 (15.6%) in gout subjects and healthy controls, respectively; even though the frequency of MetS was higher in the gout population compared to normal population, the difference was not statistically significant (OR = 1.46; 95%CI: 0.92–2.32; P = 0.102). Creatinine, Blood Urea Nitrogen, serum urate was higher while eGFR was lower in gout patients with MetS compared to those without MetS. Longer duration of gout, higher frequency of gout flare and higher Visual Analog Scale pain score were noted in gout patients with MetS compared to those without MetS. Conclusions Although MetS prevalence was numerically higher among patients with gout than controls, the between-group difference was not statistically significant. However, among patients with gout, those with MetS had less favorable renal function markers and more severe gout-related clinical characteristics, including longer disease duration, more frequent flares, and higher pain scores. Clinical trial number Not applicable.